1987
DOI: 10.1139/z87-063
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of parasite fauna of juvenile sockeye salmon (Oncorhynchus nerka) from southern British Columbian and Washington State lakes

Abstract: Sixteen species and juveniles of four taxa of parasites (Myxosporea, 4; Monogenea, 1; Trematoda, 5; Cestoda, 4; Nematoda, 2; Acanthocephala, 2; Copepoda, 2) were encountered in 1550 sockeye salmon (Oncorhynchus nerka) smolts and presmolts examined from 15 Fraser River lakes, Nimpkish Lake on Vancouver Island, and Lake Washington, Washington State, U.S.A. The most common taxa were Diphyllobothrium sp. (spp.?) plerocercoids, Philonema agubernaculum, Eubothrium sp., and Proteocephalus sp. Various statistical tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
28
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 0 publications
5
28
1
Order By: Relevance
“…Not surprisingly, our analyses showed statistically significant variation in prevalence among salmon stocks and that salmon from the central Fraser spawning zone (Quesnel, Chilko and Thompson River drainages) were 34 times more likely to be infected than those from the lower Fraser zone (Pitt, Harrison and Chilliwack Rivers). This is consistent with Bailey & Margolis (1987), who reported the parasite in 62.0 and 66.0% of smolts from Quesnel and Bowron Lakes, respectively. Interestingly, unlike In no year was n ≥ 10 for either parasite in spawning zone 1 here or in Mahony et al (2015), Bailey & Margolis (1987) found no evidence of the parasite in 244 juvenile sockeye sampled from Chilko Lake between 1976 and 1982.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Not surprisingly, our analyses showed statistically significant variation in prevalence among salmon stocks and that salmon from the central Fraser spawning zone (Quesnel, Chilko and Thompson River drainages) were 34 times more likely to be infected than those from the lower Fraser zone (Pitt, Harrison and Chilliwack Rivers). This is consistent with Bailey & Margolis (1987), who reported the parasite in 62.0 and 66.0% of smolts from Quesnel and Bowron Lakes, respectively. Interestingly, unlike In no year was n ≥ 10 for either parasite in spawning zone 1 here or in Mahony et al (2015), Bailey & Margolis (1987) found no evidence of the parasite in 244 juvenile sockeye sampled from Chilko Lake between 1976 and 1982.…”
Section: Discussionsupporting
confidence: 92%
“…The wide distribution of M. arcticus, combined with its spatial heterogeneity and apparent stability over time (Moles & Heifetz 1998, Moles & Jensen 2000 has in the past supported use of this parasite, then referred to as M. neurobius, as a biological tag to aid in the discrimination of sockeye salmon stocks in the Pacific Northwest of North America (Bailey & Margolis 1987, Quinn et al 1987). The variable prevalence of M. arcticus among salmon populations is related to conditions in salmon natal lakes that are suitable for the annelid intermediate host Stylodrilus heringianus (Kent et al 1993, Moles & Jensen 2000.…”
Section: Discussionmentioning
confidence: 99%
“…Two (G. colemanensis Mizelle & Kritsky, 1967 and G. salmonis [Yin & Sproston, 1948]) are known to have widespread geographical distributions on various salmonids in Canada and the USA (Cone et al 1983). G. nerkae Cone, Beverley-Burton, Wiles, & McDonald, 1983 is also considered a salmonid parasite (Cone et al 1983), but is known only from Oncorhynchus nerka in southern British Columbia (Bailey & Margolis 1987). G. avalonia Hanek &Threlfall, 1969 andG.…”
Section: Introductionmentioning
confidence: 99%
“…brevis Crane &Mizelle, 1967, are occasionally found on salmonid fishes, but the preferred hosts are gasterosteids and a cyprinid, respectively. Research to date on the gyrodactylids of salmonids in North America has involved mostly captive fish stocks, with a few studies describing infections on wild hosts (Hathaway & Herlevich 1973, Bailey & Margolis 1987, Frimeth 1987a. This stands in sharp contrast to the numerous studies avail able on the gyrodactylids of wild salmonids in Eurasia (Bakke et al 2007, Anttlila et al 2008, von Gersdorff Jørgensen et al 2008.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a majority of the studies in this field have focused on stock identification in different marine areas (Larsen et al, 1997;MacKenzie et al, 2008;Oliva et al, 2008;Timi and Lanfranchi, 2009), between coastal areas and estuaries (Marques et al, 2005), and among different lakes (Bailey and Margolis, 1987). Because the survival of freshwater parasites in seawater or marine parasites in freshwater would be negatively affected, the differences in the parasite communities would indicate the seasonal migration of the anadromous fish between freshwater and seawater.…”
mentioning
confidence: 99%